POLA DASAR KEMAMPUAN BACA TULIS AL-QUR’AN SESUAI DENGAN KAIDAH TAJWID - Moh Abd Azis (Jurnal Ushuluddin Adab dan Dakwah, 2018)
The Qur'an is the kalamullah which was revealed to the Prophet Muhammad. through the Angel Gabriel, as a miracle and a blessing for the universe. It contains instructions, guidelines, and lessons for those who believe and practice it, truly the glory of the Koran so that only by reading it includes worship, especially by reflecting on the meaning stored in it. The basic pattern of reading and writing ability of the Koran is one of the strategies to achieve success in learning, of course to achieve success many factors and methods are used. Among the methods used are the Baghdadiyah method, the SAS method (Synthetic Analytical Structure) and the Iqra’ method. Each of these methods has advantages and disadvantages, so that to achieve success as expected, we convert all methods to realize smooth and proficient students in reading and writing the Koran. The factors that influence the success of the learning process include internal and external factors. Where internal factors include motivation, interests and talents of students. While external factors include parents, communities and teachers who provide learning.